Suprascapular neuropathy in tennis players: A review of 27 cases - Daubinet, G. (2000)
Suprascapular neuropathy is a common shoulder injury in sports that involve a throwing motion, such as tennis. Following a review of the disorder, the results of our experience with 27 cases in professional tennis players are presented. It is very often misdiagnosed and should always be considered in the case of pain in either shoulder. Usually, conservative treatment will be required. The recovery period varies, but is often very long.